Activity of ibrutinib plus R-CHOP in diffuse large B-cell lymphoma: Response, pharmacodynamic, and biomarker analyses of a phase Ib study. (2020) - Schaffer, Michael; Chaturvedi, Shalini; Davis, Cuc; de Jong, Jan; Aquino, Regina; Oki, Yasuhiro; Fourneau, Nele; Younes, Anas; Balasubramanian, Sriram
Highlights: Biomarkers of response to ibrutinib +  R -CHOP in untreated DLBCL were assessed. High overall response rate was noted regardless of DLBCL subtype. Early minimal residual disease negativity was associated with durable response. Favorable genetic profile and young age predicted beneficial clinical outcome. Results of mutational and proteomic analyses are presented. Abstract: Introduction: This unplanned post-hoc analysis was based on data from the phase Ib DBL1002 study (NCT01569750) and evaluated the association between molecular biomarkers and clinical response to combined treatment with ibrutinib plus rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in diffuse large B-cell lymphoma (DLBCL) subtypes. Methods: DLBCL subtyping was conducted using immunohistochemistry. Next-generation sequencing using immunoglobulin H primers assessed minimal residual disease (MRD). A quantitative assay evaluated Bruton's tyrosine kinase (BTK) occupancy by ibrutinib in peripheral blood mononuclear cells. Targeted DNA sequencing examined genetic variants by DLBCL subtype. Secreted protein expression was evaluated with a SomaLogic analyte panel. Results: Among 21 patients with DLBCL (median age 53.5 years), 17 achieved a complete response (CR) and 4 a partial response (PR). Of the 11 subtyped patients, 9 had a CR (5/7 germinal center B-cell–like [GCB] and 4/4 non-GCB) and 2 had a PR (both GCB). Nine of 12 patients tested for MRD achieved early (cycle 2 day 1) MRD negativity; most had a CR. There was near-complete BTK occupancy at 4 h postdose. Mutation analysis ( n  = 19) revealed variants including CREBBP, KMT2D, LRP1B, BCL2, and TNFRSF14; only 1 CD79B and TP53 each; no CARD11 or MYD88 . Conclusions: In this study, first-line ibrutinib plus R-CHOP benefited patients with DLBCL, with good overall response rate and early MRD negativity. With a caveat of small sample size, our results showed that a favorable genetic profile and younger patient age may be important to beneficial clinical outcome with ibrutinib plus R-CHOP in DLBCL.